deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Persistence of SARS-CoV-2 S IgG Antibodies in Children Post-COVID-19 and the Association of Antibody Levels with Vaccination Status - Eduardo L. López; María S. Tineo; Federico Di Gregorio; María F. Pavan; Florencia A. Bonnin; Lidia E. Torrado; Paola J. Karp; Analía Toledano; Ana Caratozzolo; Sergio I. Nemirovsky; María M. Contrini; Lorena I. Ibañez; et al. (Current Microbiology, 2026)

Beet leaves after in vitro human gastrointestinal digestion present antioxidant capacity and protective effects in colorectal cancer cells - Luis Gustavo Saboia Ponte; Beatriz Terui Milanezi; Izabella Batista Barbosa; Isadora Carolina Betim Pavan; Ana Paula Morelli; Mariana Camargo Silva Mancini; Luiz Guilherme Salvino da Silva; Jessica Freire Feitor; Aline Teixeira do Brasil Morais; Daniel Rodrigues Cardoso; Maria Teresa Bertoldo Pacheco; Adriane Elisabete Costa Antunes; et al. (Food Research International, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Nanofiber-boosted retrograded starch/pectin microparticles for targeted 5-Aminosalicylic acid delivery in inflammatory bowel disease: In vitro and in vivo non-toxicity evaluation - Andréia Bagliotti Meneguin; Cesar Augusto Roque-Borda; Ana Beatriz Grotto Piperas; Maria Fernanda Ortolani Pollini; Vinicius Martinho Borges Cardoso; Laura Maria Duran Gleriani Primo; Forogh Alemi; Fernando Rogério Pavan; Marlus Chorilli (Carbohydrate Polymers, 2024)

Opportunities to integrate Ecosystem Services into Life Cycle Assessment (LCA): a case study of milk production in Brazil - Daiane Vitória da Silva; Ana Laura Raymundo Pavan; Luiz Carlos de Faria; Cassiano Moro Piekarski; Yovana María Barrera Saavedra; Diogo A. Lopes Silva (Ecosystem Services, 2024)

Bats (Mammalia: Chiroptera) of Ubajara National Park, Ceará, Brazil: a diversity assessment using complementary sampling methods - Ana C. Pavan; Gustavo L. Urbieta; Werther P. Ramalho; Gabryella S. Mesquita; Jeanneson Sales; Fábio Falcão; Tarcilla Valtuille (Mammal Research, 2024)

Morphological and genetic diversity in a South American forest‐dependent bat - Sofia Marques Silva; Ana Carolina Pavan; Samara Alves Barroso de Souza; Gilmax Gonçalves Ferreira; José de Sousa e Silva; Leonardo C. Trevelin (Zoologica Scripta, 2024)
The Neotropical realm is vastly known for its richness, being the Amazon one of the main cradles of taxonomic diversity in the region. In the last decades, molecular analyses have been further increasing the number of Amazonian vertebrate species, hidden under traditional taxonomy due to morphological convergence. Bats represent an interesting example, as the number of recognized bat species is continuously expanding with the identification of numerous cryptic taxa. Studies combining different lines of evidence, such as morphometric and molecular approaches, have been playing an important role in addressing knowledge gaps on Neotropical bat diversity. Within the Phyllostomidae family, the dwarf little fruit bat Rhinophylla pumilio is a forest‐dependent species, with a disjunct distribution in the Amazonian and Atlantic forests. Moreover, different karyotypes have been recovered across the species distribution, suggesting this might be one more example of cryptic diversity. Here, we test this assumption by identifying geographic patterns of morphological and molecular variation within the species' entire range of distribution. Our results point to an overall morphological and morphometric homogeneity, except between Atlantic Forest and Amazonian specimens, with significant dissimilarity among some cranial characters. Furthermore, genetic data suggest a rapid and recent diversification, with these two lineages most likely corresponding to speciating taxa. Within the Amazonian forest, our molecular analyses also recovered four additional lineages, likely encompassing intraspecific diversity. Furthermore, studies are required to confirm the need for a taxonomic rearrangement.

Trait related aberrant connectivity in clinically stable patients with schizophrenia: A seed based resting state fMRI study - Paris Alexandros Lalousis; Aanya Malaviya; Rachel Upthegrove; Kareen Heinze; Ana Diukova; Dorothee Auer; Peter Liddle; Pavan Mallikarjun (Brain Imaging and Behavior, 2022)
Aberrant resting-state connectivity within and between the Default Mode Network, the Executive Control Network, and the Salience Network is well-established in schizophrenia. Meta-analyses have identified that bilateral lingual gyrus is as the only region showing hyperactivity in schizophrenia and there are reports of increased connectivity between the lingual gyrus and other brain regions in schizophrenia. It is not clear whether these abnormalities represent state or trait markers of the illness, i.e., if they are only present during the acute phase of the illness (state) or if they reflect a predisposition to schizophrenia (trait). In this study, we used a seed-based functional connectivity analysis to investigate brain networks in schizophrenia patients who are in the stable phase of their illness and assess functional connectivity using seeds in the lingual gyrus, the posterior cingulate, the right dorsolateral prefrontal cortex (dlPFC), the right anterior insula (rAI) and the right orbital frontoinsula. Twenty patients with schizophrenia in a stable phase of their illness (as defined by the course of illness and Signs and Symptoms of Psychotic Illness (SSPI) scores) and 20 age and sex-matched healthy controls underwent resting-state functional Magnetic Resonance Imaging (rs-fMRI). Data was analysed using the Data Processing Assistant for Resting-State fMRI Advanced Edition (DPARSFA) V3.1 ( http://rfmri.org/DPARSF ) and the statistical parametric mapping software 8 (SPM8). Compared with healthy controls, patients with schizophrenia showed increased connectivity between the left lingual gyrus and the middle frontal gyrus, and the cingulate cortex. Lingual gyrus hyper-connectivity may be a stable trait neuroimaging marker for schizophrenia. Our findings suggest that aberrant connectivity in major resting-state networks may not be present after the acute illness has stabilised.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Removal of pharmaceutical compounds from aqueous solution by novel activated carbon synthesized from lovegrass (Poaceae) - Nilton F.G.M. Cimirro; Eder C. Lima; Mariene R. Cunha; Silvio L. P. Dias; Pascal Silas Thue; Ana C. Mazzocato; Guilherme L. Dotto; Marcos A. Gelesky; Flávio André Pavan (Environmental Science and Pollution Research, 2020)

Eragrostis plana Nees as a novel eco-friendly adsorbent for removal of crystal violet from aqueous solutions - Augusto Cezar D. Filho; Ana C. Mazzocato; Guilherme L. Dotto; Pascal S. Thue; Flávio A. Pavan (Environmental Science and Pollution Research, 2017)

Chromosomal characteristics of rDNA in a conserved karyotype of two Sternopygus macrurus (Gymnotiformes: Sternopygidae) populations from upper Paraná River basin - Carlos Alexandre Fernandes; Lucas Baumgärtner; Leonardo Marcel Paiz; Vladimir Pavan Margarido; Ana Luiza de Brito Portela-Castro (Biologia, 2017)

Do wood-based panels made with agro-industrial residues provide environmentally benign alternatives? An LCA case study of sugarcane bagasse addition to particle board manufacturing - Diogo Aparecido Lopes Silva; Francisco Antonio Rocco Lahr; Ana Laura Raymundo Pavan; Yovana M. B. Saavedra; Natalia Crespo Mendes; Sabrina Rodrigues Sousa; Roberta Sanches; Aldo Roberto Ometto (The International Journal of Life Cycle Assessment, 2014)

Palladium(II) imine ligands cyclometallated complexes with a potential leishmanicidal activity on Leishmania (L.) amazonensis - Lilian Pereira Franco; Elba Pereira de Góis; Bárbara Santoni Codonho; Ana Laura Raymundo Pavan; Ivan de Oliveira Pereira; Marcos José Marques; Eduardo Tonon de Almeida (Medicinal Chemistry Research, 2013)